ANALYSIS OF PREGNANT WOMEN'S MOTIVATION AND FAMILY SUPPORT ON INTEGRATED ANTENATAL CARE PARTICIPATION - Retno Palupi Yonni Siwi; Anggrawati Wulandari; Erma Retnaningtyas; Nita Dwi Astikasari (Universitas STRADA Indonesia, 2023)
Integrated ANC is very important to be given by health workers to pregnant women. The purpose of this study was to determine the analysis of motivational factors and family support for integrated ANC participation. The design is correlational analytic with cross sectional design. The population were all pregnant women with a total sampling of 20 people. The independent variables are motivation and family support, dependent variable is integrated ANC participation. The results that half of the respondents had strong motivation (50%), most of the respondents had moderate family support (55%), almost all of the respondents participated in integrated ANC (85%). There is a relationship between family motivation and integrated ANC participation (p-value = 0.006 <0.05), and there is a relationship between family support and integrated ANC participation (p-value = 0.010 <0.05). Self-awareness is able to form strong family motivation and support so as to increase integrated ANC participation